Effects of Liposome-Entrapped Muramyl Tripeptide Phosphatidylethanolamine (L-MTP-PE) on the Tumor Growth and Survival of Mice Bearing Syngeneic Tumor in Combination with a Chemotherapeutic or Immunomodulatory Agent - Tanaka, Motoharu; Abe, Shigeru (Drug Research, 2022)
Antitumor activities of L-MTP-PE (Liposome entrapped myuramyl tripeptide phosphatidylethanolamine) in the combination treatment with chemo- or immune-therapeutic antitumor agents against various syngeneic tumors were tested.Against Meth A fibrosarcoma solid tumor system, L-MTP-PE showed slight but statistically significant elongation of survival days against 5-FU monotherapy in spite of its non-effect on tumor growth, when combined with 5-FU. Against liver metastasis model of M5076 carcinoma, L-MTP-PE showed a tendency of elongation of survival days by its single drug treatment, however, elongation with statistical significance was observed in the combination treatment with 5-FU in comparison with control group.These data suggest that L-MTP-PE seems to elongate the survival days of the solid tumor bearing mice and the liver metastasis model basically due to its saving effect on chemotherapeutic drug-induced immunosuppression. In the combination with an immunotherapeutic agent in mice, TNF production induced by another biological response modifier OK-432 was potentiated when primed with L-MTP-PE. L-MTP-PE also potentiate the antitumor effect of OK-432 possibly through the enhanced production of TNF-α. Combination of L-MTP-PE and OK-432 is considered to be a candidate for a new treatment model for cancer.
Keywords: L-MTP-PE; MDP; combination therapy; OK-432